New perspectives for sampling: US and German developments and what comes next - Jütte, Bernd Justin (Sweet and Maxwell, 2017)
The use of samples from sound recordings is establihsed parctice, however its legality in absence of a license is still unclear. Two appeals in the US and in germany might have shown the direction for future cases by permittng sampling in relatively narrowly described circumstances. This article discusses potential consequences from these recet judgments and their relavance for music samling as a cultural technique.